Digital printing: relations between technology, drawing and textile surface (Revista de Ensino em Artes, Moda e Design, 2021)
Instruments and techniques used in the Textile printing process often influence the result of image reproduction. Information on the different types of digital textile printing technologies was collected through bibliographic research as well as on printed samples. For the purpose of analyzing how digital textile printing influences image reproduction, this study presents different samples with different fabrics to understand those relevant factors. 100% cotton and 100% polyester plain weave fabrics with different patterns and 100% polyester jersey were selected in the retail market for printing tests with a single file containing several images.The images were printed at three resolutions: 300, 150 and 72 PPI. The 150 PPI images were excluded from this article, as they did not have significant differences compared to theothers. The experimental results show that there are differences between the characteristics studied in the images with a resolution of 300 PPI and 72 PPI, which allows a set of practical information regarding digital printing technology on textile substrates to be organized.
Keywords: digital printing; drawing; surface design